Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae) - Frank, David (Zootaxa, 2020)
The subgenus Stigmatophorella Tôyama, 1986 of Chalcophorella Kerremans, 1903 is revised based on comparative study of extensive material including types of all described taxa. One new subspecies is described: Chalcophorella (Stigmatophorella) bagdadensis wandalii subsp. nov. from NE Iraq, NW Iran and S Armenia. Chalcophorella quadrimaculata (Redtenbacher, 1850) is removed from synonymy with C. stigmatica (Dalman, 1817), transferred from the nominotypical subgenus to Stigmatophorella and downgraded to subspecies Chalcophorella (S.) bagdadensis quadrimaculata (Redtenbacher, 1850) stat. nov., assign. nov. Two new synonymies are established: C. (S.) bagdadensis quadrimaculata = C. (S.) bagdadensis freyi Obenberger, 1942 syn. nov.; = C. (S.) bagdadensis berhauti Mandl & Pochon, 1957 syn. nov. (formerly synonym of C. (S.) bagdadensis bagdadensis). Lectotypes are designated for following taxa to ensure their correct application and recognition in future: Chalcophorella (S.) bagdadensis amarensis Obenberger, 1942; C. (S.) bagdadensis bagdadensis (Laporte de Castelnau & Gory, 1837), C. (S.) bagdadensis freyi; C. (S.) bagdadensis quadrimaculata; C. (S.) escalerae (Abeille de Perrin, 1904); C. (S.) orientalis Obenberger, 1924; and C. (S.) quadrioculata (Kollar, 1843). All herein included taxa are illustrated with colour photographs of habitus and the male aedeagus. A key to all taxa is presented.